Synthesis of Barium M-Hexaferrite Using Co-precipitation Method with Zn Doping Based on Natural Iron Sand at Tebing Beach, North Lombok as Microwave Absorbent Material - Susilawati; Aris Doyan; Thufail Mujaddid Al-Qoyyim; Putri Julia Maemum; Chorina Ika Ristanti; Baiq Istira Ariani; Ap’aludin (Postgraduate, University of Mataram, 2023)
This study aims to synthesize barium M-hexaferite using the coprecipitation method with Zn doping based on natural iron sand at the Tebing Beach of North Lombok as a microwave absorbent material. This study used 3 variations of doping concentration (x), namely x = 0.000; 0.400; and 0.800. In addition, variations in the calcination temperature were also carried out, namely 400°C and 1100°C. After the calcination stage, the sample is ground to obtain smaller or nano-sized particles. The results showed that the sample has a brick red color for a temperature of 400°C and black for a temperature of 1100°C. This shows that the higher the calcination temperature, the darker the color of the sample.